Youth Who Kill in Turkey: A Study on Juvenile Homicide Offenders, Their Offenses, and Their Differences From Violent and Nonviolent Juvenile Delinquents - Erbay, Ayhan (Journal of interpersonal violence, 2021)
This study aims to answer two major research questions: (a) What are the characteristics of the juvenile homicide offenders (JHOs) and their offenses in Turkey? (b) How do different risk factors vary across the JHOs and other violent and nonviolent juvenile offenders? The data set was derived from the court records of a group of adjudicated youth (n = 546) in Turkey. These records were coded to include information on both the offense characteristics of the homicides committed by juveniles (i.e., motivation, weapon of choice, victims’ characteristics, etc.) and the individual and family-level risk factors available in JHOs and two other delinquent groups. Our findings indicated that most of the homicide cases committed by juveniles were motivated by a fight/argument and did not involve any criminal premeditation. The victims were mostly strangers and close in age to the offenders. JHOs were significantly different from other juvenile offenders in a number of aspects, such as age, number of siblings, effectiveness of intrafamilial communication, social mobility, having risky friends, being school dropouts, and working at a paid job. However, JHOs and other juvenile offenders were not significantly different in a majority of the assessed risk factors. The findings pointed out that the risks existing at JHOs were not reflecting the stereotypical perspectives about violent delinquents. For instance, JHOs had the lowest rate of having risky friends compared with other two groups of juvenile offenders. In addition, we found that a typical homicide committed by a juvenile in Turkey was not criminally motivated, in most instances, but the outcome of an instantly escalating personal conflict between youth. In light of the study findings, we proposed several policy implications such as keeping youth in a formal education system to prevent their exposure to culturally inherent adverse social values that promote violent and revengeful reactions to a personal conflict.